EgMIXTA1, a MYB-Type Transcription Factor, Promotes Cuticular Wax Formation in Eustoma grandiflorum Leaves - Wang, Lishan; Xue, Wanjie; Li, Xueqi; Li, Jingyao; Wu, Jiayan; Xie, Linan; Kawabata, Saneyuki; Li, Yuhua; Zhang, Yang (Frontiers in Plant Science, 2020)
In the aerial plant organs, cuticular wax forms a hydrophobic layer that can protect cells from dehydration, repel pathogen attacks, and prevent organ fusion during development. The MIXTA gene encodes an MYB-like transcription factor, which is associated with epicuticular wax biosynthesis to increase the wax load on the surface of leaves. In this study, the AmMIXTA-homologous gene EgMIXTA1 was functionally characterized in the Eustoma grandiflorum. EgMIXTA1 was ubiquitously, but highly, expressed in leaves and buds. We identified the Eustoma MIXTA homolog and developed the plants for overexpression. EgMIXTA1-overexpressing plants had more wax crystal deposition on the leaf surface compared to wild-type and considerably more overall cuticular wax. In the leaves of the overexpression line, the cuticular transpiration occurred more slowly than in those of non-transgenic plants. Analysis of gene expression indicated that several genes, such as EgCER3, EgCER6, EgCER10, EgKCS1, EgKCR1, and EgCYP77A6, which are known to be involved in wax biosynthesis, were induced by EgMIXTA1-overexpression lines. Expression of another gene, WAX INDUCER1/SHINE1, encoding a transcription factor that stimulates the production of cutin, was also significantly higher in the overexpressors than in wild-type. However, the expression of a lipid-related gene, EgABCG12, did not change relative to the wild-type. These results suggest that EgMIXTA1 is involved in the biosynthesis of cuticular waxes.